Impact of Hydrological Study to Water Quality Status in Kuantan River, Pahang, Malaysia - Marcus Ata, Frankie; Khairul Amri Kamarudin, Mohd; Yaakub, Nadzifah; Abd. Wahab, Noorjima; Ekhwan Toriman, Mohd; Juahir, Hafizan; Barzani Gasim, Muhammad; ., Sunardi; Amiera Abdul Halim, Aishatul; Nizam Adha Abd Raoff, Muhammad; Najmi Haris, Muhamad (International Journal of Engineering and Technology, 2018)
Water is a vital for all aspects of human and ecosystem survival. The evaluations of water quality parameters and hydrological status are necessary to enhance the performance of an assessment operation and develop better water resources management and plan. There are three sampling stations were selected along the Kuantan River. Seven water quality parameters were measured and Malaysian Department of Environment Water Quality Index (DOE-WQI) was calculated and classified based on the National Water Quality Standard, Malaysia (INWQS). The water balance status applied to determine the stability of inflows and outflows into and from the basin. As a result, all water quality parameters (DO, COD, BOD, TSS, NH3-N and pH) which categorized under the ranged of class II until class IV respectively. Kuantan River located in Pahang state, Malaysia which is significantly degrading due to human activities as well as urbanization in and within the area. Overall, the result showed that the estimated average sediment that flows out of Kuantan Rivers is 108.88tonnes/day (24 February 2017) and 44.917 tonnes/day (30 April 2017). The contributors of sedimentation problems in Kuantan River are from unsustainable land use such as urbanization and industrialization which trapping the bed sediments and river band erosion.Â Â